Implementasi Investasi Emas: Kajian Teoritis dan Praktis Menurut Ekonomi Islam - Istan, Muhammad (Al-Intaj : Jurnal Ekonomi dan Perbankan Syariah, 2023)
The purpose of this study is to describe the concept of gold investment by business people today. Next show the concepts and views of Islamic economics regarding gold investment. The research method used is a literature review, by collecting various relevant documents. The results of the study show that there are differences of opinion in investing in gold, some prohibit it and some allow it. Scholars banned the majority of fuqaha from the Hanafi, Maliki, Shafi'i, and Hambali schools. While scholars who allow it are Ibn Taymiyah, Ibn Qayyim, and contemporary scholars. The basis of the scholars who forbid it states that gold and silver are tsaman (price, means of payment, money), which cannot be exchanged in installments or installments, because this causes usury. Meanwhile, scholars who say may put forward the argument that gold and silver are goods (sil'ah) that are sold and bought like ordinary goods, and are no longer tsaman (price, means of payment, and money). Meanwhile, in terms of benefits, investing in gold is an investment that benefits investors in the long term.